2015
DOI: 10.1089/ast.2014.1195
|View full text |Cite
|
Sign up to set email alerts
|

Descent without Modification? The Thermal Chemistry of H2O2 on Europa and Other Icy Worlds

Abstract: The strong oxidant H2O2 is known to exist in solid form on Europa and is suspected to exist on several other Solar System worlds at temperatures below 200 K. However, little is known of the thermal chemistry that H2O2 might induce under these conditions. Here, we report new laboratory results on the reactivity of solid H2O2 with eight different compounds in H2O-rich ices. Using infrared spectroscopy, we monitored compositional changes in ice mixtures during warming. The compounds CH4 (methane), C3H4 (propyne),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
(40 reference statements)
1
7
0
Order By: Relevance
“…Previous studies have revealed that thermal reactions take place in mixed ices of SO 2 and H 2 O, with the primary product being bisulphite (HSO − 3 ) alongside a smaller quantity of meta-bisulphite (S 2 O 2− 5 ) [28,29]. In the presence of oxidant species, the SO 2 may be oxidised to bisulphate (HSO − 4 ) or sulphate (SO 2− 4 ) [30][31][32][33].…”
Section: Thermal Chemistry In a Mixed Ice Containing H 2 O And Somentioning
confidence: 99%
“…Previous studies have revealed that thermal reactions take place in mixed ices of SO 2 and H 2 O, with the primary product being bisulphite (HSO − 3 ) alongside a smaller quantity of meta-bisulphite (S 2 O 2− 5 ) [28,29]. In the presence of oxidant species, the SO 2 may be oxidised to bisulphate (HSO − 4 ) or sulphate (SO 2− 4 ) [30][31][32][33].…”
Section: Thermal Chemistry In a Mixed Ice Containing H 2 O And Somentioning
confidence: 99%
“…As with the early Earth, the icy moons would, while producing copious reductants, soon face an oxidant crisis. Denitrifying methanotrophic acetogenesis might well be the emergent metabolism on such worlds, with nitrate/nitrite produced in the ice shell through the oxidation of ammonia with hydrogen peroxide entrained from the surface as electron acceptors (Loeffler and Hudson, 2015 ; Russell et al , 2017 ).…”
Section: Astrobiological Implicationsmentioning
confidence: 99%
“…In addition, H 2 S has been tentatively identified on the surface of the Galilean satellites (McCord et al 1998). Though H 2 S does not react with the oxidant H 2 O 2 in the solid phase (Loeffler & Hudson 2015), H 2 S reacts readily with the oxidant O 3 in the gas phase (Cadle & Ledford 1966;Hales et al 1969;Glavas & Toby 1975). A low-temperature thermal oxidation reaction between an additional sulfur compound and the strong oxidant O 3 may have implications for the surface and subsurface chemistry of the Galilean satellites.…”
Section: Introductionmentioning
confidence: 99%